Trace elements distribution in colloform chalcopyrite and tennantite: insights from Butte (USA) and Lisheen (Ireland) - Alexandre Cugerone; Denis Fougerouse; Max Frenzel; Kalin Kouzmanov; William D.A. Rickard; Kai Luo; Vincent Motto-Ros; Valby van Schijndel; Lorenzo Tavazzani; David W. Saxey; Steven M. Reddy (Geochimica et Cosmochimica Acta, 2026)

In-situ U-Pb ages of calcite from the Nadan Sb deposit (South China) record a ∼ 10 million years lifecycle of the hydrothermal system - Ni Peng; Dai Zhang; Alexandre Cugerone; Kai Luo; Jia-Xi Zhou (Journal of Asian Earth Sciences, 2026)

The role of ore-forming conditions in high germanium enrichment of colloform sphalerite: A case study of the Banbianjie deposit, SW China - Guotao Sun; Jia-Xi Zhou; Alexandre Cugerone; Lingli Zhou; Kai Luo; Maoda Lu (Journal of Geochemical Exploration, 2025)

Rapid crystal growth promotes the precipitation of nanoscale fluid inclusions rich in halogens and metals in colloform sphalerite - Kai Luo; Alexandre Cugerone; Denis Fougerouse; Jia-Xi Zhou; Haiyang Xian; Yiping Yang; David W. Saxey; Vincent Motto-Ros; Xiao Sun; William D.A. Rickard; Steve M. Reddy (Geochimica et Cosmochimica Acta, 2025)

Tracing fluid signature and metal mobility in complex orogens: insights from Pb-Zn mineralization in the Pyrenean Axial Zone - Alexandre Cugerone; Stefano Salvi; Kalin Kouzmanov; Oscar Laurent; Bénédicte Cenki (Mineralium Deposita, 2025)
Orogenic processes encompass a complex interplay of deformation and metamorphic events, which can impact the formation of ore deposits to various degrees. However, distinguishing fluid signatures from orogenic versus post-orogenic events presents a significant challenge due to the scarcity of robust geochemical indicators that remain unaffected during multiple post-mineral reworking events. This study carefully examines the properties and chemistry of primary and secondary fluid inclusions (FIs), identifying distinct signatures of two fluid populations linked to different styles of Pb-Zn mineralization in the Pyrenean Axial Zone (PAZ) of Southern-France/Northern-Iberia: These included late-Carboniferous stratabound epigenetic Pb-Zn deposits and Mesozoic crosscutting Pb-Zn(-Ge) vein systems. Population (I) is identified in primary and secondary FIs in a few crosscutting Pb-Zn veins and constitutes a minor component in stratabound epigenetic bodies. It exhibits Na-dominated low to intermediate salinity (< 20 wt% NaCl eq.), intermediate temperatures (200–350 °C), abundant CO 2 -rich FIs and shows low homogeneous Cl/Br molar ratios. These characteristics are consistent with a metamorphic origin of the fluids, associated with Late-Variscan metamorphism. Population (II) is commonly observed in the crosscutting vein systems where it occurs as primary and pseudosecondary FIs, as well as in stratabound epigenetic bodies where it represents the main fluid component of secondary FIs. Population (II) is Ca-dominated with intermediate to high salinity (15–35 wt% NaCl eq.), relatively low temperature (< 200 °C), and shows high Cl/Br molar ratios with significant variations. This last characteristic is typical of mixing of at least two fluids, one with a probable low Cl/Br molar ratio at shallow crustal levels and another with high Cl/Br molar ratio at deeper levels. Characteristics of population (II) are consistent with a fluid of basinal origin that interacted with the basement while circulating in the Pyrenees during the Mesozoic, although a Pyrenean-Alpine age cannot be excluded. Locally, in sphalerite-hosted secondary FIs that form trails in the crosscutting veins, we find evidence of high Ge concentrations (up to few 1000s ppm), which correlate with anomalous Pb and Tl concentrations. Very high metal concentrations (up to 1–2 wt% Pb, Zn), which are inversely proportional to Cl/Br molar ratios, are found in FIs mainly within veins hosted in deep-seated high-grade metamorphic rocks. Based on a compilation of fluid data from the literature, a first-order correlation can be deduced between the metamorphic grade of the rocks hosting the mineralization and the Pb and Zn content in the FIs. Early stratabound orebodies are considered likely sources of metal for the development of the late crosscutting vein mineralization. This study demonstrates the significance and complexity of orogen-scale fluid circulation and supports the importance of pre-existing metal enrichment in the crust, especially in high-grade metamorphic rocks as a prerequisite for the formation of Pb-Zn veins in complex multi-stage orogens.

A Paleozoic mercury mineralisation event in South China: In situ U-Pb dating and chemical compositions of calcite from the Jianyan Hg deposit - Kai Luo; Jiaxi Zhou; Alexandre Cugerone; Meifu Zhou; Yuexing Feng; Zhongguo Jin; Jianxin Zhao (Science China Earth Sciences, 2023)

Nanoscale distribution of Ge in Cu-rich sphalerite - Denis Fougerouse; Alexandre Cugerone; Steven M. Reddy; Kai Luo; Vincent Motto-Ros (Geochimica et Cosmochimica Acta, 2023)

Germanium enrichment in sphalerite with acicular and euhedral textures: an example from the Zhulingou carbonate-hosted Zn(-Ge) deposit, South China - Kai Luo; Alexandre Cugerone; Mei-Fu Zhou; Jia-Xi Zhou; Guo-Tao Sun; Jing Xu; Kang-Jian He; Mao-Da Lu (Mineralium Deposita, 2022)

Behavior of critical metals in metamorphosed Pb-Zn ore deposits: example from the Pyrenean Axial Zone - Alexandre Cugerone; Bénédicte Cenki-Tok; Manuel Muñoz; Kalin Kouzmanov; Emilien Oliot; Vincent Motto-Ros; Elisabeth Le Goff (Mineralium Deposita, 2021)